2004
DOI: 10.1074/jbc.m313732200
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Studies of the Fe(III) and Fe(II)NO Forms of Human Neuroglobin Reveal a Potential Role against Oxidative Stress

Abstract: Neuroglobin, recently discovered in the brain and in the retina of vertebrates, belongs to the class of hexacoordinate globins, in which the distal histidine coordinates the iron center in both the Fe(II) and Fe(III) forms. As for most other hexacoordinate globins, the physiological function of neuroglobin is still unclear, but seems to be related to neuronal survival following acute hypoxia. In this study, we have addressed the question whether human neuroglobin could act as a scavenger of toxic species, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
305
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(322 citation statements)
references
References 48 publications
17
305
0
Order By: Relevance
“…A major fate of NO produced during hypoxia is that it reacts with superoxide in the diffusion-limited reaction, forming peroxynitrite (ONOO 7 ), a potent oxidating and nitrating agent, whose role in cellular damage during brain hypoxia has been recognized (28). We have recently shown that in the Fe 2+ 7NO form Ngb reacts more rapidly with peroxynitrite than Hb does (29). This scavenging property may protect the neurons and contribute to their survival following hypoxic episodes.…”
Section: Neuroglobin As Scavenger Of Reactive Oxygen and Nitrogen Spementioning
confidence: 99%
See 1 more Smart Citation
“…A major fate of NO produced during hypoxia is that it reacts with superoxide in the diffusion-limited reaction, forming peroxynitrite (ONOO 7 ), a potent oxidating and nitrating agent, whose role in cellular damage during brain hypoxia has been recognized (28). We have recently shown that in the Fe 2+ 7NO form Ngb reacts more rapidly with peroxynitrite than Hb does (29). This scavenging property may protect the neurons and contribute to their survival following hypoxic episodes.…”
Section: Neuroglobin As Scavenger Of Reactive Oxygen and Nitrogen Spementioning
confidence: 99%
“…This scavenging property may protect the neurons and contribute to their survival following hypoxic episodes. Additionally, in contrast to Hb and Mb, the reaction of met (Fe 3+ ) Ngb with peroxynitrite or hydrogen peroxide does not appear to generate the cytotoxic ferryl (Fe 4+ ) species, another feature that may contribute to cellular survival (29).…”
Section: Neuroglobin As Scavenger Of Reactive Oxygen and Nitrogen Spementioning
confidence: 99%
“…In contrast with penta-coordinated globins (e.g., Hb and Mb) (28,(44)(45)(46)(47)(48)(49)(50)(51), heme-Fe(III) human Ngb apparently does not generate the heme-Fe(IV)¼ ¼O form when exposed to H 2 O 2 and peroxynitrite, another feature of Ngb that may contribute to neuronal survival after hypoxia and that may be related to heme-Fe-atom hexa-coordination (28,30,31).…”
mentioning
confidence: 99%
“…Although the exact role of hNgb in oxidative stress is still unclear, ROS scavenging ability has been suggested (35)(36)(37). Several in vitro experiments have suggested that Ngb is able to scavenge free radical (38,39). Moreover, Fordel et al observed that the intracellular H 2 O 2 level is negatively correlated with hNgb expression in eyes of mice in hypoxia/reoxygenation studies (40).…”
Section: Discussionmentioning
confidence: 99%